DNA topoisomerases as a drug target in Leishmaniasis: Structural and mechanistic insights - Kour P.; Saha P.; Sharma D.K.; Singh K. (My University, 2025)
Leishmaniasis, caused by a protozoan parasite, is among humanity's costliest banes, owing to the high mortality and morbidity ratio in poverty-stricken areas. To date, no vaccine is available for the complete cure of the disease. Current chemotherapy is expensive, has undesirable side effects, and faces drug resistance limitations and toxicity concerns. The substantial differences in homology between leishmanial DNA topoisomerase IB compared with the human counterparts provided a new lead in the study of the structural determinants that can be targeted. Several research groups explored this molecular target, trying to fill the therapeutic gap, and came forward with various anti-leishmanial scaffolds. This article is a comprehensive review of knowledge about topoisomerases as an anti-leishmanial drug target and their inhibitors collected over the years. In addition to information on molecular targets and reported scaffolds, the review details the structure-activity relationship of described compounds with leishmanial Topoisomerase IB. Moreover, the work also includes information about the structure of the inhibitors, showing common interacting residues with leishmanial topoisomerases that drive their mode of action towards them. Finally, in search of topoisomerase inhibitors at the stage of clinical trials, we have listed all the drugs that have been in clinical trials against leishmaniasis. © 2023 Elsevier B.V.